Occulter le fait divers au profit de la politique : la presse au Congo-Kinshasa - Kalokola, Adolphe Mamiki (IJRDO - Journal of Social Science and Humanities Research, 2018)
To assure his social function better, the press (the radio, the television, the newspaper) must serve mediator between the governing and governed them. For that to make, the press is judicious to grant a fundamental importance on the news that touches the daily life of the population. Among these types of information, the various facts occupy the first room. However, when one analyzes topics treaties in the public and private medias in DRC, the various facts or information of proximity are disregarded. Medias prefer to book a lot of space to what is " political " instead of true problems of citizens. Such an attitude of medias doesn’t allow the governing to write down the social problems of citizens as priority in their political diary